Comparison of SCORE-predicted risk of death due to cardiovascular events in women before and after menopause - Piskorz, Anna; Brzostek, Tomasz (Menopause Review/Przegląd Menopauzalny, 2015)
Introduction : Approximately 55% of women in Europe die from cardiovascular events, mostly as a result of coronary diseases and cerebral stroke. There is a 10-year shift in the cardiovascular risk between women and men. The risk in a 55-year-old female patient is similar to that of a 45-year-old man, thus the risk among women increases rapidly around the age of 50, when menopause prevails to occur. The purpose of the study was to assess and compare the SCORE-predicted risk of a fatal cardiovascular incident in pre- and postmenopausal women. Material and methods : The cross-sectional study was conducted as part of community nursing practice. It covered 219 women – inhabitants of Krakow, aged from 30 to 65, without clinically validated cardiovascular diseases of arteriosclerotic and/or diabetic origin, who volunteered to take part in the study. The group was divided into three subgroups: K1 – menstruating women (n = 113), K2a – women after natural menopause (n = 88), and K2b – women after surgical menopause (n = 18). The study made use of a lifestyle questionnaire, which concerned the social and economic status, and lifestyle habits including tobacco smoking. Arterial blood pressure was measured, and total cholesterol concentration in blood (mmol/l) was recorded. Results : A high (≥ 5%) level of the SCORE risk was discovered in 14.3% of postmenopausal women, as compared to 0.9% in the group of menstruating women. An average risk of a fatal cardiovascular incident during the following 10 years was significantly higher among women from groups K2a (2.61%) and K2b (2.32%) as compared to K1 – menstruating women (0.38%). No difference was, however, discovered between groups of naturally (K2a) and surgically menopausal women (K2b). Conclusions : A significantly higher risk of SCORE-predicted death caused by a cardiovascular incident, as compared to the group of women in the premenopausal period, is characteristic of women in the postmenopausal period.